Global Research Trends on Coastal Climate Change: A Bibliometric Review Toward Supporting Mitigation Strategies - Silahooy, Veince Benjamin; Silahooy, Charles (MAKILA, 2025)
This study uses a bibliometric approach to analyze the causes and solutions to climate change. Keyword visualization indicates that recent research has focused on blue carbon and remote sensing as key methods for monitoring climate change. The countries with the highest research contributions are the United States, China, Germany, the United Kingdom, and Australia. Leading authors in this field include Agneta Andersson, Jianfeng Li, Ning Lin, and Marta Marcos. The findings identify the primary causes of climate change, which include greenhouse gas emissions, energy use, land-use change, industry, and transportation, with the highest percentage attributed to energy consumption and natural resource exploitation (35.2%). The use of fossil fuels, coal, gas, and overall energy consumption are identified as major contributors to climate change in coastal regions. As solutions, four main approaches have been identified: adopting renewable energy, sustainable practices, policy and regulatory measures, and environmental restoration. This study concludes that green technologies, supportive policies, and energy efficiency are crucial to mitigating climate change. These findings provide a comprehensive perspective on the causes and solutions to climate change, serving as a valuable reference for global environmental policy formulation.